Contribuições da COMSAÚDE na construção do conhecimento em Comunicação para a Saúde: resgate histórico e tendências dessa linha de pesquisa - Pessoni, Arquimedes (2005)
The present work research dues to a historical rescue, focusing the birth and development of research lines in Health Communication, mapping its academic area in the USA, Brazil and Latin America. We do show the main research groups in Brazil, in both spaces Communication and Health and make an analysis of papers which contributed to Brazilian Conference in Communication for Health, willing for research lines consolidation, making a comparative analysis in between all works, papers and authors showed on - all this compared to all that has been produced under the form of thesis, papers, essays, in other Brazilian universities, so as well in north american literature. It was used the exploratory, documentary and analysis of content for the accomplishment of the thesis that pointed the diffusion of innovations as root of the line of research in Health Communication.